ANALISIS POLA KONSUMSI RUMAH TANGGA PETANI GANYONG (Canna edulis Ker.) DI DESA JAPAN KECAMATAN DAWE KABUPATEN KUDUS - Lu’lu’a Ulyn Ni'mah; Shofia Nur Awami; Suprapti Supardi; Endah Subekti (Politeknik Pertanian Negeri Kupang, 2020)
This research aimed to determine the level of energy and protein consumption, share of food expenditure and the level of food security of ganyong farmer households in Japan Village Dawe Sub District Kudus Regency. The basic method in this research was descriptive analysis. Determination of location samples and respondents was done by purposive sampling technique. The total respondents were 26 ganyong farmers in Japan Village. The data used is primary data and secondary data. The results showed that the average energy consumption of ganyong farmer households was 1,947.73 kcal/person/ day and protein consumption was 59.04 grams/ person/day. Household expenditure consists of food expenditure and non-food expenditure. Ganyong farmer household food expenditure share is 48.9% while the share of non-food expenditure is 51.1%. This case shows that ganyong farmer households have high welfare or food sufficiency. The condition of food sufficiency of ganyong farmer households in Japan Village based on their level is food resistance by 53.8%, food insecurity by 11.5% and food shortages by 34.6%.